A revision of Metapontius (Siphonostomatoida: Artotrogidae) with the description of a new species associated with an octocoral from Eniwetok Atoll, Marshall Islands (USA) - Johnsson, Rodrigo; Neves, Elizabeth G. (Zootaxa, 2005)
The Artotrogidae is among the most primitive of siphonostomatoid families. Their preferred hosts, as well as precise nature of their symbiotic relationship with the host, remain uncertain despite more than a hundred years of occasional descriptions of new species and genera. Metapontius is one such case. The genus, erected in 1923 by Hansen to accommodate a single species, has remained monospecific and no other record of this species has been provided. Samples collected by Dr. Arthur Humes in 1969 at Eniwetok Atoll, and left aside for future studies, remained untouched for more than 30 years and among them a new species belonging to Metapontius was found. The main differences between the two species are the number of antennule segments, the shape of the cephalosome, the length of the siphon and the setation of legs 1 and 4. In addition, several other characters of the genus such as the antennal exopod and setation of maxillule and legs 2 and 3 are described for the first time.